2022
DOI: 10.3390/cancers14215446
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Truncated Fatty Acid–Porphyrin Conjugates Provide Photo-Sensitizer Activity for Photodynamic Therapy in Malignant Mesothelioma

Abstract: Clinical trials evaluating intrapleural photodynamic therapy (PDT) are ongoing for mesothelioma. Several issues still hinder the development of PDT, such as those related to the inherent properties of photosensitizers. Herein, we report the synthesis, photophysical, and photobiological properties of three porphyrin-based photosensitizers conjugated to truncated fatty acids (C5SHU to C7SHU). Our photosensitizers exhibited excellent water solubility and high PDT efficiency in mesothelioma. As expected, absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Due to its better loading profile, C5SHU PS was used to assess whether the PSs could impact the delivery of oxaliplatin from EVs by co-loading C5SHU and oxaliplatin. Using the oxaliplatin loading efficiency of 18.7% to normalize treatments ( Figure 2 C), EVs were co-incubated with 187 µM oxaliplatin either alone or in combination with 25 µM or 250 µM C5SHU to develop oxa-C5S-EVs with effective concentrations close to the oxaliplatin EC50 of 10 µM ( Figure 2 A) and the bioactive concentration of C5SHU [ 41 ]. SW480 CRC cells were then incubated with oxa-C5SHU-EVs, and delivery was monitored using the LA-ICP-MS platform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its better loading profile, C5SHU PS was used to assess whether the PSs could impact the delivery of oxaliplatin from EVs by co-loading C5SHU and oxaliplatin. Using the oxaliplatin loading efficiency of 18.7% to normalize treatments ( Figure 2 C), EVs were co-incubated with 187 µM oxaliplatin either alone or in combination with 25 µM or 250 µM C5SHU to develop oxa-C5S-EVs with effective concentrations close to the oxaliplatin EC50 of 10 µM ( Figure 2 A) and the bioactive concentration of C5SHU [ 41 ]. SW480 CRC cells were then incubated with oxa-C5SHU-EVs, and delivery was monitored using the LA-ICP-MS platform.…”
Section: Resultsmentioning
confidence: 99%
“…Porphyrins and other PSs are known to be cytotoxic and are used for photodynamic therapy [ 41 , 49 ] as they have radical-producing activity outside of cells. We observed that C5SHU porphyrins did not influence the viability of EVs even after exposure to light, and more interestingly, did not significantly influence the release of chemotherapy agents from EVs after light exposure—although a trend towards increased release of co-loaded oxaliplatin was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation